A Modified Delphi Study to Prioritize Content for a Simulation‐based Pediatric Curriculum for Emergency Medicine Residency Training Programs. Issue 4 (12th December 2019) - Mitzman, Jennifer; Bank, Ilana; Burns, Rebekah A.; Nguyen, Michael C.; Zaveri, Pavan; Falk, Michael J.; Madhok, Manu; Dietrich, Ann; Wall, Jessica; Waseem, Muhammad; Wu, Teresa; McQueen, Alisa; et al.
Abstract: Objectives: Pediatric training is an essential component of emergency medicine (EM) residency. The heterogeneity of pediatric experiences poses a significant challenge to training programs. A national simulation curriculum can assist in providing a standardized foundation of pediatric training experience to all EM trainees. Previously, a consensus‐derived set of content for a pediatric curriculum for EM was published. This study aimed to prioritize that content to establish a pediatric simulation‐based curriculum for all EM residency programs. Methods: Seventy‐three participants were recruited to participate in a three‐round modified Delphi project from 10 stakeholder organizations. In round 1, participants ranked 275 content items from a published set of pediatric curricular items for EM residents into one of four categories: definitely must, probably should, possibly could, or should not be taught using simulation in all residency programs. Additionally, in round 1 participants were asked to contribute additional items. These items were then added to the survey in round 2. In round 2, participants were provided the ratings of the entire panel and asked to rerank the items. Round 3 involved participants dichotomously rating the items. Results: A total of 73 participants participated and 98% completed all three rounds. Round 1 resulted in 61 items rated as definitely must, 72 as probably should, 56 as possibly could, 17 as should not, and 99 new items were suggested. Round 2 resulted in 52 items rated as definitely must, 91 as probably should, 120 as possibly could, and 42 as should not. Round 3 resulted in 56 items rated as definitely must be taught using simulation in all programs. Conclusions: The completed modified Delphi process developed a consensus on 56 pediatric items that definitely must be taught using simulation in all EM residency programs (20 resuscitation, nine nonresuscitation, and 26 skills). These data will serve as a targeted needs assessment to inform the development of a standard pediatric simulation curriculum for all EM residency programs.